Survival from Maternal Cardiac Arrest Complicating Coronavirus Disease 2019 - Andrea D. Shields; John J. Byrne; Meghan Munisteri; Michael Wood (Case Reports in Obstetrics and Gynecology)
Introduction. Coronavirus disease 2019 (COVID-19) has been linked to significant cardiovascular complications such as cardiac arrest, which are associated with a poor prognosis in adults. Little is known about the cardiac complications, specifically cardiac arrest, of COVID-19 during pregnancy and postpartum periods. Case. We present a case of survival and full neurological recovery after maternal cardiac arrest associated with COVID-19 in a postpartum female. Her postpartum course was also associated with seizures attributed to posterior reversible encephalopathy syndrome. After 19 days in the hospital, she was discharged home neurologically intact. Conclusion. More information is needed to determine the range of short- and long-term cardiac complications that may be associated with COVID-19 during pregnancy and postpartum. Additionally, pregnant patients with COVID-19 may be more likely to survive cardiac arrest compared to the general population.